2015
DOI: 10.1371/journal.pone.0133061
|View full text |Cite
|
Sign up to set email alerts
|

How to Receive More Funding for Your Research? Get Connected to the Right People!

Abstract: Funding has been viewed in the literature as one of the main determinants of scientific activities. Also, at an individual level, securing funding is one of the most important factors for a researcher, enabling him/her to carry out research projects. However, not everyone is successful in obtaining the necessary funds. The main objective of this work is to measure the effect of several important factors such as past productivity, scientific collaboration or career age of researchers, on the amount of funding t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
96
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(100 citation statements)
references
References 37 publications
4
96
0
Order By: Relevance
“…Mote arrays could help fill in gaps from the current spatially "patchy" research effort [35] and thus enhance the resulting quality of research output. In addition to increasing productivity [28], collaborative projects are a requisite from many funding agencies, and as such these consortiums are likely to appeal to funders for both small-and large-scale grants [5,13]. However, because the data collected by Motes are not necessarily associated with their owners name or with information on what the transmitting device was deployed on, an ethical code of conduct should be developed to maximize the integrity of this new way of collecting messages from satellite-linked devices [9].…”
Section: Discussionmentioning
confidence: 99%
“…Mote arrays could help fill in gaps from the current spatially "patchy" research effort [35] and thus enhance the resulting quality of research output. In addition to increasing productivity [28], collaborative projects are a requisite from many funding agencies, and as such these consortiums are likely to appeal to funders for both small-and large-scale grants [5,13]. However, because the data collected by Motes are not necessarily associated with their owners name or with information on what the transmitting device was deployed on, an ethical code of conduct should be developed to maximize the integrity of this new way of collecting messages from satellite-linked devices [9].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, tracking the actual level of collaboration (both that contained in the original proposal as well as ex post published co-authorships) may be important, especially if this is one of the goals of the research funding program. In fact, it has been shown that receiving more funding may be a result of increased collaboration (Ebadi and Schiffauerova, 2015) and may result in larger future collaborations (Adams et al, 2005). While research into collaborative scientific activities is extensive, only a few studies have looked at this directly with regard to peer review decisions; both Melin and Danell (2006) and Langfeldt et al (2012) found successful applicants have a higher degree of ex-post international co-authorship than unsuccessful applicants and both El-Sawi et al (2009) , 2016).…”
mentioning
confidence: 99%
“…Some studies highlight the importance of structural collaboration network positions as a driver of preferential attachments (Barabasi et al 2002;Moody 2004;Abbasi et al 2012). Others try to understand if the location of a researcher in a network can bring some advantages, for instance, a higher level of citations, better access to knowledge sources, awareness of potential projects or access to more funding (Abbasi et al 2011;Ebadi and Schiffauerova 2015). However, to the best of our knowledge, there is no evidence yet on the impact of structural collaboration network positions on the level of collaboration with industry.…”
Section: Network Position As Correlate Of Performancementioning
confidence: 99%